Pemanfaatan E-Commerce untuk Optimalisasi Penjualan dan Pemasaran Produk Shopsock Berbasis Web - Elisa Mei Sintiasari; Donna Setiawati; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2021)
Shopsock is one type of business in the field of shoe sales, so far the sale of shopsock products has been carried out by interacting with direct consumers and the marketing is not optimal. To optimize product sales and marketing, in this study an online sales website (e-commerce) was built to display information on products sold in shopsock stores and customers can easily make purchases. This website was built using the waterfall method, object modeling using UML, open source programming tools based on PHP, MySQL database and the result achieved is an e-commerce website to expand market prey for promotion and make it easier for consumers to buy shopsock products